Uji Validitas dan Reliabilitas Leadership Behavior Inventory, Personal Mastery Questionnaire dan Kuesioner Kinerja Perawat di Rumah Sakit - Kornelis Nama Beni; Nursalam Nursalam; M Hasinuddin (FORIKES, 2020)
Background: Measurement instruments play an important role in research, clinical practice, and health assessment. Measurement nurse leadership behavior, self-mastery and performance using the Leadership Behavior Inventory (LBI), Personal Mastery Questionnaire and nurse performance questionnaire in quality and patient safety. This instrument has been tested for validity and reliability. The aim of this study was to tested the validity and reliability of the Leadership Behavior Inventory, Personal Mastery questionnaire and nurse performance questionnaire in quality and patient safety. Method: This study was used quantitative study, a type of research tested questionnaire with a cross-sectional study design. Researchers was conducted validity and reliability tests. Respondents in this study were nurses who worked in hospitals in East Nusa Tenggara as many as 20 responden. The instruments tested were Leadership Behavior Inventory, Personal Mastery questionnaire and nurse performance questionnaire in quality and patient safety. Results: The results showed that the validity tested used Pearson product moment on 29 items of Leadership Behavior Inventory found values ( r = 0.539 – 0.938), Cronbach alpha ( 0.9 75) ; 17 Personal mastery Questionnaire items were found (r = 0.625-0.902), Cronbach alpha ( 0.9 59) ; 23 nurse performance questionnaire items were found (r = 0.714-0.942), Cronbach alpha ( 0.9 82); so that all items of this instrument was valid and reliable at a significance level of 0.0 5 . Conclusion: Leadership Behavior Inventory Instrument, Personal Mastery Questionnaire and nurse performance questionnaire was valid and reliable to measured nurse leadership, personal mastery and nurse performance in quality and patient safety. Keywords: LBI; Personal Mastery Questionnaire; nurse performance questionnaire ABSTRAK Latar Belakang: Instrumen pengukuran memainkan peran penting dalam penelitian, praktik klinis, dan penilaian kesehatan. Pengukuran perilaku kepemimpinan perawat, penguasaan diri dan kinerja menggunakan Leadership Behavior Inventory, Personal Mastery Questionnaire dan kuesioner kinerja perawat dalam mutu dan keselamatan pasien. Instrumen dilakukan uji validitas dan reliabilitas. Tujuan penelitian ini menguji validitas dan reliabilitas Leadership Behavior Inventory, Personal Mastery questionnaire dan kuesioner kinerja perawat dalam mutu dan keselamatan pasien. Metode: Penelitian ini merupakan penelitian kuantitatif, jenis penelitian testing kuesioner dengan rancangan penelitian cross-sectional. Peneliti melakukan uji validitas dan reliabilitas. Responden dalam penelitian ini adalah perawat yang bekerja di Rumah Sakit di Nusa Tenggara Timur sebanyak 20 orang. Instrumen yang diuji adalah Leadership Behavior Inventory, Personal Mastery questionnaire dan kuesioner kinerja perawat dalam mutu dan keselamatan pasien. Hasil: Hasil uji validitas menggunakan Pearson product moment pada 29 item Leadership Behavior Inventory ditemukan nilai (r = 0.539 – 0.938), Cronbach alpha (0.975); 17 item Personal Mastery Questionnaire ditemukan (r = 0.625-0.902), Cronbach alpha (0.959); 23 item kuesioner kinerja perawat ditemukan (r = 0.714-0.942), Cronbach alpha (0.982); sehingga semua item instrumen ini adalah valid dan reliabel pada taraf signifikansi 0.05. Kesimpulan: Leadership Behavior Inventory, Personal Mastery Questionnaire dan kuesioner kinerja perawat telah memenuhi validitas dan reliabilitas untuk mengukur kepemimpinan, personal mastery perawat dan kinerja perawat dalam mutu dan keselamatan pasien. Kata Kunci: LBI; Personal Mastery Questionnaire; kuesioner kinerja perawat